2019
DOI: 10.2196/12769
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Level of Knowledge About Surgical Site Infections and Risks of Wound Infection Among Medical Physicians in King Abdulaziz University Hospital: Cross-Sectional Study

Abstract: BackgroundSurgical site infections (SSIs) are one of the leading causes of death, and its prevention is a key element of applying the concept of patient safety and quality care.ObjectiveThis study aimed to assess the level of knowledge about SSIs and risks of wound infection among medical physicians in King Abdulaziz University Hospital.MethodsAll surgical and medical consultants, specialists, residents, and medical interns were invited to participate in the study. A 20-Item multiple-choice questionnaire was d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 13 publications
5
13
0
Order By: Relevance
“…Concerning factors, patients aged 54 and above had significant association with the occurrence of bedsore when compared with participants who are younger in age. This finding is similar with the study report on age showed a significant association with prevalence of bed sore in King Abdulaziz University Hospital [23], Atlantic salmon [24], [39]. This might be due to advancing in age may limited mobility, cause poor nutrition, accompanying co-morbidities, incontinence, impaired sensory perception, altered tissue perfusion, organ system failure, and infection and extrinsic factors like force and duration of pressure, shearing, friction and macerations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Concerning factors, patients aged 54 and above had significant association with the occurrence of bedsore when compared with participants who are younger in age. This finding is similar with the study report on age showed a significant association with prevalence of bed sore in King Abdulaziz University Hospital [23], Atlantic salmon [24], [39]. This might be due to advancing in age may limited mobility, cause poor nutrition, accompanying co-morbidities, incontinence, impaired sensory perception, altered tissue perfusion, organ system failure, and infection and extrinsic factors like force and duration of pressure, shearing, friction and macerations.…”
Section: Discussionsupporting
confidence: 90%
“…Several factors were contributed to pressure ulcer development. These were intrinsic factors such as advanced age (>65 years), limited mobility, poor nutrition, co-morbidities, incontinence impaired sensory perception, altered tissue perfusion, organ system failure, and infection and extrinsic factors like force and duration of pressure, shearing, friction and macerations [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The results of our study are in consistent with another study conducted in Saudi Arabia(SA) showing low level of knowledge was found among 119 doctors including intern doctors, resident doctors, and specialist doctors. This study showed that most of the doctors had fair or poor knowledge regarding the de nition, incidence, prevention of SSI [6].…”
Section: Discussionmentioning
confidence: 80%
“…(SSI) can be prevented or reduced by many methods which could decrease the costs and are highly effective as surgical scrubbing, nutritional support, preoperative bathing, mechanical bowel preparation, use of oral antibiotics, hair removal, and surgical site skin preparation and this can be achieved simply by medical awareness [6]. Every year more than 2-3 million Muslims from different countries come to Makkah for the hajj season which represent one of the largest mass gathering events worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…found that around one-third of physicians had poor knowledge regarding surgical site infections. [ 29 ] Again, this points to patients' knowledge being influenced by the physicians. From patients' collaboration perspective, most of patients were not involved in the health care delivery process.…”
Section: Discussionmentioning
confidence: 99%